Oral cancer: Recent breakthroughs in pathology and therapeutic approaches - Surekha Ramachandran (Oral Oncology Reports)
Oral cancer, primarily oral squamous cell carcinoma (OSCC), continues to be a major global health challenge. Despite improvements in early detection and treatment, the prognosis for patients, particularly those diagnosed at advanced stages, remains unfavorable. However, recent progress in understanding the molecular mechanisms of oral carcinogenesis and the development of innovative treatment approaches offer new hope for enhancing patient outcomes. This review highlights the latest discoveries in oral cancer pathology, key molecular drivers of disease progression, early detection strategies, and cutting-edge treatment options, including immunotherapy and targeted treatments. Additionally, it explores next-generation treatments incorporating artificial intelligence and machine learning.